Pemahaman Soteriologi Alkitabiah Mahasiswa Kristen UNS Surakarta - T. Haryono; Kezia Yemima (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2020)
Christian students haven’t fully understand biblical soteriology, This contidion is made worse by the effect of Christian Religious Education course to christian students’ understanding on biblical soteriology that remain unknown. This research aims to understand the effect of Christian Religious Education course to christian students’ understanding on biblical soteriology. The research uses quantitative approach with one group pretest postest method. Population inthis research is 41 Christian Bachelor’s program students of 2019 takingChristian Religious Education course at Faculty of Engineering of SebelasMaret University (UNS). Research findings: (1) Christian Religious Educationcourse give 13.5 % understanding of christian students on biblical soteriology;(2) Christian Religious Education course affected by teaching intensity, varietyof teaching methods, and course material.